Rice Husk Silica Supported Oil Palm Fruit Ash as a Catalyst in the Transesterification of Waste Frying Oil - Gaanty Pragas, Maniam; Neshabran, Ramachandran; Noor, Hindryawati; M. M., Yusoff (2014)
An investigation was conducted on palm oil palm fruit ash (OPFA), OPFA supported by rice husk silica (RHS), and potassium-OPFA-RHS as catalysts for methyl esters production through transesterification process using waste frying oil. The catalysts showed longer lasting activity than the traditional alkali catalysts. The optimum conditions for the process were: OPFA and K-OPFA-RHS catalyst amount 3 %; OPFA-RHS catalyst amount 5 %; methanol to oil molar ratio 9:1; and a reaction duration is 2 h. The process was able to transesterify oil to methyl esters at 96.6–98.2 % conversion at 65 C for all series. The catalysts were easily separated from the reaction mixture by filtration and able to be reused. Reusability up to 5 cycles is feasible with ME content above 83 %. The final product met selected biodiesel fuel properties in accordance with European Standard EN 14214.